Extracellular annexins in hemostasis system - Zhernossekov, D.D.; Roka-Moiia, Y.M.; Grinenko, T.V. (Вiopolymers and Cell, 2016)
Annexins are calcium-binding proteins that interact with cellular membranes due to their ability to bind phospholipids. The structural and functional peculiarities of these proteins have been described. Being cytosolic proteins, annexins also possess extracellular activities. However, there are some controversial opinions concerning the functional role of extracellular annexins in the human hemostasis system. We have made an attempt to summarize the latest data and consider some ideas of possible annexin application in medical practice. Анексини – це кальцій-залежні протеїни, що взаємодіють з клітинними мембранами завдяки їх властивості зв’язувати фосфоліпіди. Структурно-функціональні особливості цих протеїнів надані в науковій літературі. Хоча анексини – цитозольні протеїни, для них притаманна позаклітинна активність. Існують суперечливі дані стосовно ролі позаклітинних анексинів у системі гемостазу. Ми спробували систематизувати сучасні наукові дані та виявити можливе застосування анексинів у медичній практиці. Аннексины – это кальций-зависимые протеины, взаимодействующие с клеточными мембранами благодаря их способности связывать фосфолипиды. Структурно-функциональные особенности этих белков описаны в научной литературе. Хотя аннексины – цитозольные протеины, для них показана внеклеточная активность. Существуют противоречивые мнения касательно функциональной роли внеклдеточных аннексинов в системе гемостаза. Мы предприняли попытку систематизировать последние научные данные и рассмотреть возможное применение аннексинов в медицинской практике.